Soil conditioner based on improvement of water retention capacity of Shajiang black soil and application method of soil conditioner

By grafting nano-zeolite adsorbents on the surface of modified humic acid interpenetrating resin, a soil conditioner was prepared, which solved the problem of poor water retention of sand ginger black soil, achieved long-term water absorption and water retention effects, and improved soil structure and cadmium reduction capabilities. .

CN119350110AActive Publication Date: 2025-01-24INST OF SOIL & FERTILIZER ANHUI ACAD OF AGRI SCI

Patent Information

Application Number
CN202411906518.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-01-24
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The poor water retention performance of sand ginger black soil leads to weak drought resistance and poor structural properties, which affects the timely water supply and groundwater utilization of crops.

Method used

By preparing nano -breaked stones adsorbent and branches on the surface of the resin on modified humimonic acid, the water preservation agent powder is formed, and the soil conditioning agent is prepared in combination with other components to improve its water retention performance.

Benefits of technology

Realize the effects of long -term water absorption and water preservation, maintain soil oxidation and restoration characteristics, effectively exert ingredients to reduce cadmmid reduction, improve the soil structure, and enhance ventilation and water retention.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 6764DDD0A0F8B
    Figure 6764DDD0A0F8B
Patent Text Reader

Abstract

The invention discloses a soil conditioner based on increasing the water retention capacity of Shajiang black soil and an application method of the soil conditioner, and belongs to the field of soil remediation fertilizers.The soil conditioner is obtained by evenly mixing water-retaining agent powder, organic fertilizer, microbial compound inoculants and corn straw; the water-retaining agent powder and an acrylic monomer generate modified humic acid interpenetrating resin powder through grafting modification of humic acid on acrylic acid, and a nano zeolite adsorbent loaded with nano zero-valent iron is fixed on the surface of the modified humic acid interpenetrating resin; the soil conditioner has the characteristics of long-acting water absorption and water retention, reduction of soil bulk density, improvement of soil porosity, maintenance of redox characteristics of soil, effective reduction of cadmium, and improvement of the slow release property of the fertilizer and the microbial compound inoculant; the organic fertilizer can improve the fertility of the soil; the compound microbial inoculants can improve the disease resistance and yield of crops; corn straw contains abundant nutrient elements and organic matters and is a high-quality organic fertilizer source.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of soil remediation fertilizers, and in particular relates to a soil conditioner for increasing the water retention performance of sand ginger black soil and an application method thereof. Background Art

[0002] Sandy black soil is a semi-hydromorphic soil formed by de-swamping on river-lake sediments under warm temperate semi-humid climate conditions, mainly affected by local factors and biological factors. Its profile configuration is black soil layer-de-swamping layer-sandy layer. Within the 1.5m control layer section, there must be two basic layers of black soil layer and sandy layer at the same time, and the thickness of recent light-colored sediments covering the black soil layer must be less than 60cm.

[0003] The texture of sand ginger black soil is heavy, with poor permeability, poor drainage and poor supply capacity from the lower layer to the upper layer, which is prone to waterlogging, waterlogging and drought. These characteristics lead to the weak drought resistance of sand ginger black soil, which is the main reason for the soil's proneness to drought. The structure of sand ginger black soil is poor, and it contains more sand ginger, which occupies a certain space in the soil, affecting the soil's water holding capacity. The water supply capacity and water supply intensity of sand ginger black soil are both small, which is not conducive to the timely water supply of crops. At the same time, the capillary water in the soil rises slowly and the rising height is small, which is not conducive to the use of groundwater by crops.

[0004] Chinese patent application CN113444529A discloses a soil conditioner for treating heavy metal pollution in cultivated land and a preparation method thereof, wherein zeolite, quicklime, hydroxyapatite, composite algae powder, sodium-modified bentonite, magnesium silicate, potassium sulfoselenide, nano zero-valent iron, modified molybdenum disulfide and humic acid resin are uniformly mixed. However, after the soil conditioner is applied to sand ginger black soil, it is difficult to fully exert its cadmium-reducing effect due to the poor water retention of the sand ginger black soil, which affects the redox characteristics of the soil. Summary of the invention

[0005] The purpose of the present invention is to provide a soil conditioner based on increasing the water retention performance of sand ginger black soil and an application method thereof, a nano zeolite adsorbent loaded with nano zero-valent iron is fixed on the surface of a modified humic acid interpenetrating resin to prepare a water retaining agent powder, and other components are combined to prepare a soil conditioner that helps to improve the water retention of sand ginger black soil. After being applied to the sand ginger black soil, a long-term water retention effect is achieved, which helps to maintain the redox characteristics of the soil and effectively exerts the cadmium reduction effect of the nano zeolite adsorbent.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A method for applying a soil conditioner for increasing the water retention performance of sand ginger black soil comprises the following steps: Spread 1000-2000kg / mu soil conditioner on the surface of the soil to be treated, then plow and stir the soil to be treated together with the conditioner spread on it 3-4 times according to the tillage and stirring method, with a turning depth of 20-25cm, and sow after 7-10 days.

[0007] The soil conditioner is prepared by the following steps: Step 1: add humic acid powder, 1 / 2 of the total amount of acrylic acid solution and deionized water into a reactor, introduce nitrogen protection, stir and react at 95-100° C. and 500-600 r / min for 1-2 hours, cool to 55-65° C., add sodium sulfite as an initiator, the remaining acrylic acid solution and hydroxymethyl acrylamide as a cross-linking agent into the reactor, heat to 70-80° C., stir at 500-600 r / min for 3-4 hours, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry at 60-80° C. for 1-2 hours to obtain modified humic acid interpenetrating resin powder.

[0008] Step 2: Add 60-70% NaOH solution, sodium aluminum silicate and sodium silicate into the reactor, stir at 60-70°C and 200-300r / min for 1-2h, cool naturally, mix aluminum sulfate, 70-80% concentrated sulfuric acid solution and deionized water evenly and add them into the reactor, continue stirring and reacting for 1-2h, seal the obtained mixed solution in a 5L polytetrafluoroethylene stainless steel reactor, heat to 90-100°C, statically crystallize for 30-35 hours, wash the crystals with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry at 60-80°C for 1-2h to obtain nano zeolite powder.

[0009] Step 3: Add nano zeolite powder, 5-hydroxyisophthalic acid and deionized water to a reactor, dissolve sodium hexadecyl sulfate as a surfactant in an ethanol aqueous solution with a mass fraction of 70-75% and add it to the reactor, stir for 1-2 hours at 50-60°C and 400-500r / min, add zinc sulfate to the reactor, continue stirring and reacting for 1-2 hours, introduce nitrogen protection, add ferrous sulfate heptahydrate to the reactor, and drop a 60-70% potassium borohydride solution into the reactor at a rate of 30-40mL / min. After the dropwise addition is completed, continue the reaction for 4-5 hours, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times, respectively, and vacuum dry at 60-80°C for 16-18 hours to obtain a nano zeolite adsorbent.

[0010] Step 4: Add the modified humic acid interpenetrating resin powder and deionized water into the reactor, heat to 40-50°C, stir and react at 500-600r / min for 40-50min, then add the nano zeolite adsorbent into the reactor, continue stirring and reacting for 2-3h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, vacuum dry at 60-80°C for 1-2h, and crush to obtain water retaining agent powder.

[0011] Step 5: Add water-retaining agent powder, organic fertilizer, microbial compound agent and crushed corn stalks into a blender and mix them evenly to obtain a soil conditioner based on increasing the water-retaining performance of sand ginger black soil.

[0012] Furthermore, in step 1, the usage ratio of humic acid powder, acrylic acid solution, deionized water, sodium sulfite and hydroxymethyl acrylamide is 4-6kg: 2-2.4L: 2-3L: 1-2kg: 1-2kg.

[0013] Furthermore, in step 1, the neutralization degree of the acrylic acid solution is 65-70%, and the concentration of acrylic acid in the acrylic acid solution is 6-7 mol / L.

[0014] Furthermore, in step 2, the usage ratio of NaOH solution, sodium aluminum silicate, sodium silicate, aluminum sulfate, concentrated sulfuric acid solution and deionized water is 1.2-1.5L:4-6kg:4-5kg:1-2kg:1-1.2L:2-3L.

[0015] Furthermore, in step three, the dosage ratio of nano zeolite powder, 5-hydroxyisophthalic acid, deionized water, sodium hexadecyl sulfate, ethanol aqueous solution, zinc sulfate and potassium borohydride solution is 2-3kg:2-3kg:2-3L:1-1.2L:1-2L:1-2kg:1-1.2kg:900-1000mL.

[0016] Furthermore, in step 4, the usage ratio of the modified humic acid interpenetrating resin powder, deionized water and nano zeolite adsorbent is 3-4 kg: 4-6 L: 3-4 kg.

[0017] Furthermore, in step five, the usage ratio of water retaining agent powder, organic fertilizer, microbial compound agent and corn straw is 10-15kg: 1-2kg: 1-2kg: 10-15kg.

[0018] Beneficial effects of the present invention: 1. The soil conditioner prepared by the present invention has the characteristics of long-term water absorption and water retention, which helps to improve the problem of poor water retention of sand ginger black soil, maintain the redox characteristics of the soil, and effectively play a cadmium-reducing role; improve the soil structure, help to enhance the aeration of the soil, and make the soil more loose.

[0019] Soil conditioners contain water-retaining agent powder, organic fertilizer, microbial compound agent and corn straw. Organic fertilizer can improve soil fertility, and microbial compound agent can increase crop disease resistance and yield; corn straw is rich in nitrogen, phosphorus, potassium, calcium, magnesium and other nutrients and organic matter, and is a high-quality source of organic fertilizer.

[0020] 2. The nano-zeolite adsorbent of the present invention is grafted on the surface of the modified humic acid interpenetrating resin powder, and has the characteristics of large water absorption, fast water absorption speed, strong water retention capacity and long water retention time. Humic acid can react chemically with minerals in the soil to form stable soil aggregates, thereby improving the soil structure, helping to enhance the air permeability, water permeability and water retention of the soil, and making the soil looser; although humic acid has good hydrophilicity, the physical structure formed by the original intermolecular force after absorbing water is easily destroyed. The interpenetrating network structure can help maintain the original physical structure, so that it can better maintain the structure after absorbing water, and improve the service life and stability.

[0021] 3. The nano zeolite adsorbent of the present invention has strong ion exchange and adsorption capacity. The nano zeolite adsorbent surface adsorbs a large amount of nano zero-valent iron, which can undergo redox reactions with heavy metal ions, reducing heavy metal ions to metal form, and itself is oxidized to Fe 3+ It further combines with heavy metal ions to form solid or dissolved precipitation, thereby effectively removing heavy metal pollution in the soil. The metal skeleton structure generated in situ on the surface of nano zeolite has a strong adsorption capacity, which can stabilize the nano zero-valent iron and prevent it from agglomeration and oxidation. It is grafted on the surface of the interpenetrating network structure and evenly dispersed, further isolating oxygen, thereby extending the service life of the nano zero-valent iron; and by grafting on the surface of the interpenetrating network structure, the contact area with the heavy metals in the soil is increased, further enhancing the adsorption of heavy metals.

[0022] 4. The water-retaining agent powder of the present invention has the ability of high porous water absorption and high adsorption, and can tightly bind the effective nutrients in the fertilizer and the effective bacteria of the microbial composite agent inside through the pore adsorption force and the electrostatic attraction of anions and cations, further improving the slow release of the fertilizer and reducing nutrient loss. After being mixed with the microbial composite agent, it can be used as a carrier material to protect the microbial composite agent from environmental factors, improve its survival rate and activity, and can slowly release the microbial composite agent, increase its activity in the soil, and through the immobilization effect of the carrier, the microbial composite agent can better contact with the soil and improve its utilization rate. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0024] Example 1: A soil conditioner based on increasing the water retention performance of sand ginger black soil is prepared by the following steps: S1: 4 kg humic acid powder, 1 L acrylic acid solution with a neutralization degree of 65% and 2 L deionized water were added to a reactor, nitrogen was introduced for protection, and the reaction was stirred at 95°C and 500 r / min for 1 h. The reaction was cooled to 55°C, and 1 kg sodium sulfite as an initiator, 1 L acrylic acid solution with a neutralization degree of 65% and 1 kg hydroxymethyl acrylamide as a cross-linking agent were added to the reactor. The reaction was heated to 70°C, stirred at 500 r / min for 3 h, filtered, and the filter cake was washed twice with deionized water and anhydrous ethanol respectively, and dried at 60°C in vacuo for 1 h to obtain modified humic acid interpenetrating resin powder.

[0025] Acrylic acid monomers undergo polymerization reaction under the action of initiators to form polyacrylic acid. At the same time, the phenolic hydroxyl groups of humic acid form ester bonds with the carboxyl groups on the polyacrylic acid chains. In addition to chemical bonding, the polymer chains of humic acid and acrylic acid can be physically entangled with each other. This physical entanglement also increases stability and helps to form a uniform, highly water-soluble interpenetrating network structure.

[0026] S2: Add 1.2L of 60% NaOH solution, 4kg of sodium aluminum silicate and 4kg of sodium silicate into the reactor, stir at 60°C and 200r / min for 1h, cool naturally, mix 1kg of aluminum sulfate, 1L of 70% concentrated sulfuric acid solution and 2L of deionized water and add them into the reactor, continue stirring and reacting for 1h, seal the obtained mixed solution in a 5L polytetrafluoroethylene stainless steel reactor, heat to 90°C, and statically crystallize for 35h, wash the crystals twice with deionized water and anhydrous ethanol respectively, and vacuum dry at 60°C for 1h to obtain nano zeolite powder.

[0027] S3: 2 kg of nano zeolite powder, 2 kg of 5-hydroxyisophthalic acid and 2 L of deionized water were added to a reactor, 1 L of sodium hexadecyl sulfate as a surfactant was dissolved in 1 L of 70% ethanol aqueous solution and added to the reactor, stirred at 50°C and 400 r / min for 1 h, 1 kg of zinc sulfate was added to the reactor, the stirring reaction was continued for 1 h, nitrogen was introduced for protection, 1 kg of ferrous sulfate heptahydrate was added to the reactor, 900 mL of 60% potassium borohydride solution was added dropwise to the reactor at a rate of 30 mL / min, and after the addition was completed, the reaction was continued for 4 h, filtered, the filter cake was washed twice with deionized water and anhydrous ethanol respectively, and vacuum dried at 60°C for 16 h to obtain a nano zeolite adsorbent.

[0028] The surface of the nano zeolite is rich in (Si-OH), which undergoes esterification reaction with the carboxyl group of 5-hydroxyisophthalic acid, and a metal skeleton is generated in situ on the surface of the nano zeolite under the action of zinc sulfate and the surfactant sodium hexadecyl sulfate; ferrous sulfate heptahydrate is reduced to nano zero-valent iron by potassium borohydride in an oxygen-free environment and adsorbed on the nano zeolite and the metal skeleton.

[0029] S4: Add 3 kg of modified humic acid interpenetrating resin powder and 4 L of deionized water into a reactor, heat to 40°C, and stir at 500 r / min for 40 min. Then add 3 kg of nano zeolite adsorbent into the reactor, continue stirring for 2 h, filter, wash the filter cake twice with deionized water and anhydrous ethanol respectively, dry under vacuum at 60°C for 1 h, and crush to obtain water retaining agent powder.

[0030] The (Si-OH) on the surface of nano-zeolite can chemically bond with the carboxyl group on the surface of the modified humic acid interpenetrating resin powder, so that it is fixed on the resin surface, thereby obtaining a water-retaining agent powder with high water absorption, high adsorption and water retention.

[0031] S5: 10 kg of water retaining agent powder, 1 g of organic fertilizer, 1 kg of microbial compound agent and 10 kg of crushed corn stalks are added into a blender and mixed evenly to obtain a soil conditioner based on increasing the water retaining performance of sand ginger black soil.

[0032] Example 2: A soil conditioner based on increasing the water retention performance of sand ginger black soil is prepared by the following steps: S1: 5 kg humic acid powder, 1.1 L acrylic acid solution with a neutralization degree of 68% and 2.5 L deionized water were added to a reactor, nitrogen was introduced for protection, and the reaction was stirred at 95°C and 500 r / min for 1.5 h. The reactor was cooled to 60°C, and 1.5 kg sodium sulfite as an initiator, 1.1 L acrylic acid solution with a neutralization degree of 68% and 1.1 kg hydroxymethyl acrylamide as a cross-linking agent were added to the reactor. The reactor was heated to 75°C, stirred at 550 r / min for 3.5 h, filtered, and the filter cake was washed with deionized water and anhydrous ethanol for 3 times respectively, and vacuum dried at 70°C for 1.1 h to obtain modified humic acid interpenetrating resin powder.

[0033] S2: 1.4L of 65% NaOH solution, 5kg of sodium aluminum silicate and 4.5kg of sodium silicate were added into the reactor, stirred at 65°C and 250r / min for 1.1h, cooled naturally, 1.5kg of aluminum sulfate, 1.1L of 75% concentrated sulfuric acid solution and 2.5L of deionized water were mixed evenly and added into the reactor, and the stirring reaction was continued for 1.1h. The obtained mixed solution was sealed in a 5L polytetrafluoroethylene stainless steel reactor, heated to 95°C, and statically crystallized for 33h. The crystals were washed 3 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 68°C for 1.5h to obtain nano zeolite powder.

[0034] S3: 2.5 kg of nano zeolite powder, 2.5 kg of 5-hydroxyisophthalic acid and 2.5 L of deionized water were added to the reactor, 1.1 L of sodium hexadecyl sulfate as a surfactant was dissolved in 1.5 L of 73% ethanol aqueous solution and added to the reactor, stirred at 55°C and 450 r / min for 1.5 h, 1.5 kg of zinc sulfate was added to the reactor, the stirring reaction was continued for 1.5 h, nitrogen was introduced for protection, 1.1 kg of ferrous sulfate heptahydrate was added to the reactor, 950 mL of 65% potassium borohydride solution was added dropwise to the reactor at a rate of 35 mL / min, and after the addition was completed, the reaction was continued for 4.5 h, filtered, the filter cake was washed 3 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 65°C for 17 h to obtain a nano zeolite adsorbent.

[0035] S4: Add 3.5 kg of modified humic acid interpenetrating resin powder and 5 L of deionized water into a reactor, heat to 45 ° C, stir and react at 550 r / min for 48 minutes, then add 3.5 kg of nano zeolite adsorbent into the reactor, continue to stir and react for 2.5 hours, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, dry it in a vacuum at 68 ° C for 1.5 hours, and crush it to obtain a water retaining agent powder.

[0036] S5: 13 kg of water retaining agent powder, 1.5 kg of organic fertilizer, 1.5 kg of microbial compound agent and 13 kg of crushed corn stalks are added into a blender and mixed evenly to obtain a soil conditioner based on increasing the water retaining performance of sand ginger black soil.

[0037] Example 3: A soil conditioner based on increasing the water retention performance of sand ginger black soil is prepared by the following method: S1: 3 kg humic acid powder, 600 mL acrylic acid solution with a neutralization degree of 70% and 3 L deionized water were added to a reactor, nitrogen was introduced for protection, and the reaction was stirred at 100°C and 600 r / min for 2 h. The reaction was cooled to 65°C, and 2 kg sodium sulfite as an initiator, 900 mL acrylic acid solution with a neutralization degree of 70% and 2 kg hydroxymethyl acrylamide as a cross-linking agent were added to the reactor. The reaction was heated to 80°C, stirred at 600 r / min for 4 h, filtered, and the filter cake was washed with deionized water and anhydrous ethanol for 3 times respectively, and vacuum dried at 80°C for 2 h to obtain modified humic acid interpenetrating resin powder.

[0038] S2: Add 900mL of 70% NaOH solution, 4k sodium aluminum silicate and 5kg sodium silicate into the reactor, stir at 70℃ and 300r / min for 2h, cool naturally, mix 2kg aluminum sulfate, 600mL of 80% concentrated sulfuric acid solution and 3L deionized water evenly and add into the reactor, continue stirring and reacting for 2h, seal the obtained mixed solution in a 5L polytetrafluoroethylene stainless steel reactor, heat to 100℃, statically crystallize for 35h, wash the crystals with deionized water and anhydrous ethanol for 3 times respectively, and vacuum dry at 80℃ for 2h to obtain nano zeolite powder.

[0039] S3: 3 kg of nano zeolite powder, 3 kg of 5-hydroxyisophthalic acid and 3 L of deionized water were added to a reactor, 1.2 L of sodium hexadecyl sulfate as a surfactant was dissolved in 2 L of 75% ethanol aqueous solution and added to the reactor, stirred at 60°C and 500 r / min for 2 h, 2 kg of zinc sulfate was added to the reactor, stirring and reacting for 2 h, nitrogen was introduced for protection, 900 g of ferrous sulfate heptahydrate was added to the reactor, 600 mL of 70% potassium borohydride solution was added dropwise to the reactor at a rate of 30 mL / min, and after the addition was completed, the reaction was continued for 5 h, filtered, the filter cake was washed 3 times with deionized water and anhydrous ethanol respectively, and vacuum dried at 60°C for 18 h to obtain a nano zeolite adsorbent.

[0040] S4: Add 4 kg of modified humic acid interpenetrating resin powder and 6 L of deionized water into a reactor, heat to 50°C, and stir at 600 r / min for 50 min. Then add 4 kg of nano zeolite adsorbent into the reactor, continue stirring for 3 h, filter, wash the filter cake with deionized water and anhydrous ethanol for 3 times respectively, dry under vacuum at 80°C for 2 h, and crush to obtain water retaining agent powder.

[0041] S5: 15 kg of water retaining agent powder, 2 kg of organic fertilizer, 2 kg of microbial compound agent and 15 kg of crushed corn stalks are added into a blender and mixed evenly to obtain a soil conditioner based on increasing the water retaining performance of sand ginger black soil.

[0042] The microorganisms in the microbial composite agent include Bacillus subtilis, Bacillus licheniformis and actinomycetes, with an effective bacterial count ≥ 1 billion / g and organic matter ≥ 50%.

[0043] The present invention also provides a method for applying a soil conditioner based on increasing the water retention performance of sand ginger black soil: Spread 1000-2000kg / mu soil conditioner on the surface of the soil to be treated, then plow and stir the soil to be treated together with the conditioner spread on it 3-4 times according to the tillage and stirring method, with a tillage depth of 20-25cm, and sow after 7-10 days.

[0044] Comparative Example 1: Commercially available humic acid powder, nano zeolite, nano zero-valent iron, animal feces, microbial composite agent and crushed corn stalks were directly added into a blender in a mass ratio of 10:16:1:4:2:10 and mixed evenly to obtain a soil conditioner.

[0045] Comparative Example 2: Based on Example 3, the humic acid powder and the nano zeolite adsorbent in step S3 were directly mixed in a mass ratio of 1:1 to prepare a soil conditioner as a water retaining agent powder, and the other steps remained unchanged.

[0046] Comparative Example 3: Based on Example 3, in step S4, the nano zeolite adsorbent is replaced with the nano zeolite powder of the same mass in step S2, and the other steps remain unchanged to prepare a soil conditioner.

[0047] Comparative Example 4: Based on Example 3, nano zeolite powder and nano zero-valent iron were uniformly mixed in a mass ratio of 1:1 to prepare a soil conditioner as a nano zeolite adsorbent, and the other steps remained unchanged.

[0048] In the embodiments and comparative examples: The model of the polytetrafluoroethylene stainless steel reactor is RNKL-PTFE5L; Humic acid powder was purchased from Shanxi Jiayou Humic Acid Technology Co., Ltd.; Nano-zero-valent iron was purchased from Shanghai Maoguo Nanotechnology Co., Ltd.; Sodium sulfite, sodium aluminum silicate, sodium silicate, ferrous sulfate heptahydrate, zinc sulfate, potassium borohydride, sodium hexadecyl sulfate, and 5-hydroxyisophthalic acid were purchased from Sigma-Aldrich.

[0049] Organic fertilizers, microbial compound agents and corn straw are all commercially available products.

[0050] Performance tests were carried out on Examples 1 to 3 and Comparative Examples 1 to 3. 1000 kg / mu of soil conditioner was spread on the surface of the soil to be treated, and then the soil to be treated together with the conditioner spread thereon was plowed and stirred 3 times according to the plowing and stirring method. The plowing depth was 20 cm to obtain different test soil samples.

[0051] 1. Place the test soil sample 6 months after the application of soil conditioner vertically in pure water for 10 hours, with the water level exceeding the top of the test soil sample, so that the test soil sample can fully absorb water until saturated, then take out different test soil samples, weigh them and place them vertically on a grid, weigh them every 1.5 hours at room temperature until the mass of the test soil sample no longer changes, that is, it loses water to a constant weight, record the mass before water absorption and the mass after full water absorption, calculate the water absorption (water absorption = mass after full water absorption - mass before water absorption), so as to evaluate the water absorption capacity of the test soil sample after the application of different soil conditioners, record the time when the mass no longer changes for the first time, and record it as the water retention time, so as to evaluate the water absorption and water retention capacity of the test soil sample after the application of different soil conditioners, and retest the water absorption and water retention time of the same batch of test soil samples in the 12th month.

[0052] 2. Refer to "Soil Testing Part 4: Determination of Soil Bulk Density" (NY / T1121.4-2006): Use a ring knife to take different test soil samples, make sure the ring knife is full of soil, weigh the total mass of the ring knife and wet soil, dry the ring knife and soil in an oven to constant weight, then weigh the mass after drying, calculate the soil bulk density based on the mass of the dried soil and the volume of the ring knife, bulk density (g / cm³) = (m2-m1) / V×(1-W / 1000); then based on the soil bulk density and soil specific gravity, use the formula: soil porosity = (1-soil bulk density / soil specific gravity) × 100%, calculate the soil porosity, and evaluate the air permeability and tightness of the soil after applying different soil conditioners.

[0053] m2 is the mass of the cutter ring and wet soil (g); m1 is the mass of the cutter ring (g); V is the volume of the cutter ring (cm³); W is the soil moisture content (g / kg).

[0054] 3. The cadmium content of different test samples was measured after applying different soil conditioners for 6 months and 12 months according to the method of ISO 10381-4:2003, so as to evaluate the migration and transformation of heavy metals in the soil.

[0055] 4. Refer to the national standard (GB / T23348-2009): The nitrogen release of soil conditioners in the same time is determined by performing room temperature extraction at 25°C and rapid extraction at 100°C. The nutrient release rates of different soils are compared by these two methods.

[0056] 5. Take 25g of test soil sample and 225mL of sterile water to prepare a 1:10 soil suspension. Then, take 1mL from the homogenous solution and add it to 9mL of sterile saline to prepare a 1:100 homogenous solution. Then, take 1mL from the homogenous solution and add it to 9mL of sterile saline to prepare a 1:1000 diluted homogenous solution. After Gram staining of the soil suspension, make agar slices with a thickness of 2.5mm, observe and count the number of colonies under an optical microscope at 10×100 times, so as to evaluate the sustained release and protective effects of different soil conditioners on the microbial composite agent.

[0057] The results are shown in Table 1: Table 1 It can be seen from Table 1 that the water absorption and water retention time of the soil conditioners prepared in Examples 1 to 3 of the present invention are significantly better than those of the comparative example. The nano zeolite adsorbent is grafted on the surface of the modified humic acid interpenetrating resin powder, which increases the water absorption and prolongs the water retention time. The interpenetrating network structure helps to maintain the original physical structure of the humic acid, so that it can better maintain the structure after absorbing water, thereby improving the service life and stability.

[0058] The soil bulk density in Examples 1 to 3 is significantly lower than that in the comparative example, but the soil porosity is significantly better than that in the comparative example 1. Humic acid can react chemically with minerals in the soil to form stable soil aggregates, thereby improving the soil structure, helping to enhance the aeration of the soil and making the soil more loose. The cadmium content in Examples 1 to 3 is significantly lower than that in the comparative example 1 to 3. A large amount of nano-zero-valent iron is adsorbed on the surface of the nano-zeolite adsorbent, which can undergo an oxidation-reduction reaction with heavy metal ions to reduce the heavy metal ions to a metallic form, and is oxidized to Fe 3+ It further combines with heavy metal ions to form solid or dissolved precipitation, and the interpenetrating network structure increases the contact area with heavy metals in the soil, further enhancing the adsorption of heavy metals.

[0059] The cadmium content in Comparative Example 4 is lower than that in Comparative Examples 1 to 3 but higher than that in Example 3. This may be because the metal skeleton structure generated in situ on the surface of the nano zeolite has a strong adsorption capacity, which can stabilize the nano zero-valent iron and prevent its agglomeration and oxidation. It is grafted on the surface of the interpenetrating network structure and evenly dispersed, further isolating oxygen, thereby extending the service life of the nano zero-valent iron.

[0060] The nitrogen release amount in Examples 1 to 3 is significantly lower than that in Comparative Example 1, and the number of effective bacteria is significantly better than that in Comparative Example 1. The water-retaining agent powder can be prepared, and the effective nutrients in the fertilizer and the effective bacteria of the microbial composite agent can be tightly bound inside through the pore adsorption force and the electrostatic attraction of anions and cations, further improving the sustained release of the fertilizer, protecting the microbial composite agent, improving its survival rate and activity, and allowing the microbial composite agent to be slowly released.

[0061] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.

[0062] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A soil conditioner based on increasing the water retention performance of sand ginger black soil, characterized in that: The components include the following by mass: 10-15 parts of water retaining agent powder, 1-2 parts of organic fertilizer, 1-2 parts of microbial compound agent and 10-15 parts of corn stalk powder; The water-retaining agent powder is prepared by the following steps: Step 1: Add nano zeolite powder, 5-hydroxyisophthalic acid and deionized water to a reactor, then dissolve sodium hexadecyl sulfate in a 70-75wt% ethanol aqueous solution and add the solution to the reactor, stir at 50-60°C and 400-500r / min for 1-2h, then add zinc sulfate and continue stirring to react for 1-2h, add ferrous sulfate heptahydrate to the reactor under nitrogen protection, then drop 60-70wt% potassium borohydride solution to the reactor, continue to react for 4-5h after the dropwise addition is complete, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dry to obtain a nano zeolite adsorbent; Step 2: Add the modified humic acid interpenetrating resin powder and deionized water into the reactor, stir and react at 40-50°C and 500-600r / min for 40-50min, then add the nano zeolite adsorbent into the reactor, continue stirring and reacting for 2-3h, filter, wash the filter cake with deionized water and anhydrous ethanol for 2-3 times respectively, vacuum dry, and crush to obtain water retaining agent powder.

2. A soil conditioner based on increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: The nano zeolite powder is prepared by the following steps: A 60-70wt% NaOH solution, sodium aluminum silicate and sodium silicate are added to a reactor, stirred at 60-70°C and 200-300r / min for 1-2h, cooled naturally, aluminum sulfate, 70-80wt% concentrated sulfuric acid solution and deionized water are evenly mixed and added to the reactor, and the stirring reaction is continued for 1-2h. The obtained mixed solution is sealed in a 5L polytetrafluoroethylene stainless steel reactor, heated to 90-100°C, statically crystallized for 30-35 hours, the crystals are washed 2-3 times with deionized water and anhydrous ethanol respectively, and vacuum dried to obtain nano zeolite powder.

3. A soil conditioner based on increasing the water retention performance of sand ginger black soil according to claim 2, characterized in that: The dosage ratio of the NaOH solution, sodium aluminum silicate, sodium silicate, aluminum sulfate, concentrated sulfuric acid solution and deionized water is 1.2-1.5L: 4-6kg: 4-5kg: 1-2kg: 1-1.2L: 2-3L.

4. A soil conditioner based on increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: The modified humic acid interpenetrating resin powder in step 2 is prepared by the following steps: Humic acid powder, 1 / 2 of the total amount of acrylic acid solution and deionized water are added to a reactor, nitrogen protection is introduced, the reaction is carried out at 95-100° C. and 500-600 r / min for 1-2 hours, the reaction is cooled to 55-65° C., sodium sulfite, the remaining acrylic acid solution and hydroxymethyl acrylamide are added to the reactor, the reaction is heated to 70-80° C., the reaction is stirred at 500-600 r / min for 3-4 hours, the reaction is filtered, the filter cake is washed with ionized water and anhydrous ethanol for 2-3 times respectively, and vacuum dried to obtain modified humic acid interpenetrating resin powder; the neutralization degree of the acrylic acid solution is 65-70%.

5. A soil conditioner based on increasing the water retention performance of sand ginger black soil according to claim 4, characterized in that: The usage ratio of the humic acid powder, acrylic acid solution, deionized water, sodium sulfite and hydroxymethyl acrylamide is 4-6kg: 2-2.4L: 2-3L: 1-2kg: 1-2kg.

6. A soil conditioner for increasing the water retention performance of sand ginger black soil according to claim 4, characterized in that: The concentration of acrylic acid in the acrylic acid solution is 6-7 mol / L.

7. A soil conditioner for increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: The dosage ratio of the nano zeolite powder, 5-hydroxyisophthalic acid, deionized water, sodium hexadecyl sulfate, ethanol aqueous solution, zinc sulfate and potassium borohydride solution in step 1 is 2-3kg: 2-3kg: 2-3L: 1-1.2L: 1-2L: 1-2kg: 1-1.2kg: 900-1000mL.

8. A soil conditioner for increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: In step 2, the usage ratio of the modified humic acid interpenetrating resin powder, deionized water and nano zeolite adsorbent is 3-4 kg: 4-6 L: 3-4 kg.

9. The method for applying a soil conditioner for increasing the water retention performance of sand ginger black soil according to claim 1, characterized in that: The steps include: Spread the soil conditioner on the surface of the treated soil at a rate of 1000-2000kg / mu, then plow and stir the treated soil together with the conditioner spread on it 3-4 times with a plowing depth of 20-25cm, and sow after 7-10 days.

Citation Information

Patent Citations

  • Soil conditioner for treating heavy metal pollution of cultivated land and preparation method thereof

    CN113444529A

  • Microorganism composite bacterium agent and preparation method and application thereof

    CN101054552A

  • Compound water-retaining agent for soil as well as preparation method and application of compound water-retaining agent

    CN104263376A

  • Humic acid-based composite water retaining agent and preparation method thereof

    CN108948293A

  • Water-retaining compound fertilizer and preparation method thereof

    CN112624853A

Cited By

  • Bovine woolskin biomass organic fertilizer and preparation method thereof

    CN121342601A